RELEVANSI DIMENSI KUALITAS PELAYANAN DAN PUASAN PELANGGAN BAGI PENGUNJUNG MUSEUM Di TAMAN MINI INDONESIA INDAH - Kusumasitta Kusumasitta (Jurnal Manajemen dan Pemasaran Jasa, 2014)
This research study about the effect of tourism on local people's needs and extent to which the benefits to the community museum in Taman Mini Indonesia Indah and also evaluation of service quality to improve visitor satisfaction. The method used in this research is by using a questioner data that spread out through Taman MiniIndonesia Indah customer for knowing their satifaction level. After the data gathered, then it divide into five kind variable (Tangible, Reability, Responsiveness, Assurance & Empathy). The result of this research conclude that : The tangible asset(X1), The reliability(X2), The Responsiveness(X3), The Assurance(X4), TheEmphaty(X5), is giving positive influence and significantly in customer satisfaction.Keywords : Tangible, reability, responsiveness, assurance, empathy,customer satisfaction.